Macroeconomic volatility and international integration. - Arespa-Castelló, Marta (John Wiley & Sons Ltd, 2014)
This paper explores the effects that varying degrees of international openness have on macroeco- nomic volatility. The analysis is conducted for a two-symmetric-country world under three levels of international integration: that of a closed economy, a financial autarky, and full financial integration. Different degrees of trade openness are considered in the form of home biases, while the economy is left vulnerable to total factor productivity and innovation shocks. Full financial integration is found to reduce firm-size volatility and volatility in the mass of operative firms following a productivity shock and to increase them after an innovation shock. Moreover, the interaction between interna- tional sharing of profits and terms of trade transmissions determines the non-linear behaviour of consumption-to-output ratio volatility found in empirical studies.
Keywords: Macroeconomía; Integración económica; Precios; Economic integration; Financial integration; Trade openness; Volatility